Cost-Related Non-Adherence to Prescribed Medicines: What Are Physicians' Moral Duties? - Ghinea, Narcyz; Hutchison, Katrina; Lotz, Mianna; Rogers, Wendy A. (American Journal of Bioethics, 2025)
As the price of pharmaceuticals and biologicals rises so does the number of patients who cannot afford them. In this article, we argue that physicians have a moral duty to help patients access affordable medicines. We offer three grounds to support our argument: (i) the aim of prescribing is to improve health and well-being which can only be realized with secure access to treatment; (ii) there is no morally significant difference between medicines being unavailable and medicines being unaffordable, so the steps physicians are willing to take in the first case should extend to the second; and (iii) as the primary stakeholder with a duty to put the individual patient's interests first, the medical professional has a duty to address cost-barriers to patient care. In articulating this duty, we take account of important epistemic and control conditions that must be met for the attribution of this duty to be justified.